IMPLEMENTASI PROGRAM ADIWIYATA DI SD NEGERI BHAYANGKARA YOGYAKARTA - Dwi Nurdiati; Dholina Inang Pambudi (Universitas Ahmad Dahlan, 2018)
SD Negeri Bhayangkara Yogyakarta is one of the Adiwiyata schools in DIY Province that implements the Adiwiyata program. The purpose of this research is to know the implementation of Adiwiyata program as well as to know the supporting factors and factors inhibiting the implementation of Adiwiyata program in Bhayangkara State Elementary School Yogyakarta.The type of this research is descriptive qualitative. Subjects used are principals, Adiwiyata school teams, students, and teachers. Meanwhile, the object of this research is the implementation of Adiwiyata program in Bhayangkara State Elementary School. Data collection was obtained through interview, observation, and documentation.The results of Adiwiyata program implementation in Bhayangkara State Elementary School based on four components are as follows. 1) Environmentally sound policies are contained in school vision, mission and objectives, curriculum structure content integrated with PPLH efforts, and RKAS schools allocated 20% for PPLH activities. The inhibiting factor of this policy is that there are some students who have no concern for the environment. 2) The environment-based curriculum uses the 2013 curriculum containing environmental materials. The inhibition of environmental curriculum is the existence of some teachers who are less understanding and less creative in developing learning.Participatory activities involving all members of the school and community elements to participate in PPLH activities. But there are still some parents who have not fully understood the activities of the school. 4) Eco-friendly facilities and infrastructure owned quite a lot and quite complete and used for learning. But there are still some facilities and infrastructure that have not been used optimally.